Treatment and outcomes for locally recurrent rectal cancer in Norway - Ghazwan Al Haidari; Arne M. Solbakken; Linn Merete Åsli; Eva Skovlund; Christine Undseth; Marianne Grønlie Guren (Acta Oncologica)
Background: The rate of locally recurrent rectal cancer (LRRC) in Norway has decreased due to advancements in surgical techniques and preoperative treatments. Despite this, LRRC continues to present significant morbidity and mortality challenges. This study aims to analyze survival outcomes following different treatment modalities for LRRC in Norway and assess the impact of changes in treatment strategies over time.